2020
DOI: 10.3390/electronics9101731
|View full text |Cite
|
Sign up to set email alerts
|

Backstepping Fuzzy Sliding Mode Control for the Antiskid Braking System of Unmanned Aerial Vehicles

Abstract: This paper proposes a backstepping fuzzy sliding mode control method for the antiskid braking system (ABS) of unmanned aerial vehicles (UAVs). First, the longitudinal dynamic model of the UAV braking system is established and combined with the model of the electromechanical actuator (EMA), based on reasonable simplification. Subsequently, to overcome the higher-order nonlinearity of the braking system and ensure the lateral stability of the UAV during the braking process, an ABS controller is designed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…e proposed fuzzy PID can improve the robustness but also increase the complexity of the control system [21]. As an effective control method to deal with the nonlinearity and robustness of ABS, sliding mode control still relies on the mathematical model of the ABS [22]. When the dynamic characteristics of the ABS are not modeled or the disturbance quantity is too large, the tracking response speed of the slip rate and the high-frequency tremor of braking torque restrict its application.…”
Section: Introductionmentioning
confidence: 99%
“…e proposed fuzzy PID can improve the robustness but also increase the complexity of the control system [21]. As an effective control method to deal with the nonlinearity and robustness of ABS, sliding mode control still relies on the mathematical model of the ABS [22]. When the dynamic characteristics of the ABS are not modeled or the disturbance quantity is too large, the tracking response speed of the slip rate and the high-frequency tremor of braking torque restrict its application.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned literature mainly implemented the LKC by controlling the steering system, which could influence the vehicle running stability. With the development of control theory, the sliding mode control methods were improved in theory and application greatly for the robustness and fast response [20,21]. Levant et al studied the k-order filter and time delay in sliding mode [22].…”
Section: Introductionmentioning
confidence: 99%
“…So, the elimination of the chattering phenomenon has attracted more and more attention recently. For example, adaptive sliding mode control [14,15], fuzzy sliding mode control [16], discrete-time sliding mode control [8,17], neural dynamic sliding mode control [18] and integral sliding mode control [19] have been proposed to mitigate the adverse effects of the chattering phenomenon. It has been reported that designing a continuous sliding mode control law to replace the discontinuous law, e.g., continuous TSMC (CTSMC) can reduce the impact of the chattering [20,21].…”
Section: Introductionmentioning
confidence: 99%